Design and production specifications of machine for wood cement composite boards production (2013)
Manual method of producing wood cement composites (WCCs) is time consuming, labour intensive and leads to inconsistent products. This paper reports the design and production specifications for a machine capable of automating the critical processes of mixing, blending, vibrating and compacting involved in WCC production for rural usage at a cottage level. It is a semi-continuous manually operated machine, made up of two broad units: the mixer and the former (conveyor cum press). The mixer is hand powered by a lever 500mm long at an average speed of 35rpm and has a capacity of 0.1514m3. The former is made up of rollers interconnected with chain drives and a freely rotating press roll. It is powered by a manually operated pulley system at an average speed of 4rpm. The mixer can save up to 52% of the total time required to achieve homogenous mix while the former can also reduce time required for board formation by 50%. The machine has an overall capacity of producing 30 Nos. of 12.5mm × 570mm × 570mm boards.